(untitled) (Research, Society and Development, 2021)
The aim of this paper was to assess the biocompatibility and expression of metalloproteinase -9 of two dentin bonding agents in human teeth, using different methods of dentin pre-treatment and different time intervals. Deep Class I cavities were prepared on the occlusal surface of 18 sound molars. Restorations were performed with XP Bond™ (Dentsply) and Futurabond® DC (VOCO). After 30, 90 or 120 days, the teeth were extracted and processed for histological and immunohistochemical assessment. In XP Bond group, was observed a moderate inflammatory infiltrate and immunoreactivity of metalloproteinase -9 in all storage intervals. In Futurabond DC group, a slight inflammatory infiltrate was found in the first intervals. After 120 days, the inflammatory infiltrate was either slight or absent, while the tissue morphology remained normal. The immunoreactivity of metalloproteinase -9 was considered moderate, except for two specimen after 120 days, that demonstrated no immunoreactivity. Therefore, etch-and-rinse adhesives exhibited a more intense pulpal response than self-etching agents. When performing adhesive restorations in medium and deep cavities in human teeth, the use of a self-etching adhesive strategy should be considered in view of the lower induction of inflammatory and proteolytic activity. Further studies of molecular events should be conducted, taking into consideration the possible inflammatory pulp reactions that can contribute to the success of restorative procedures.